Border Trade: An Effective Way for Border Rural Revitalization in the New Era (JOURNAL OF ADVANCES IN LINGUISTICS, 2022)
Rural revitalization in border areas is an important part of rural revitalization in China. Border trade plays a positive role in implementing national policies to benefit the people, attracting border people back to border areas, consolidating border security, promoting ethnic integration and sharing the fruits of development. The potenti al of border trade can be fully stimulated by policy optimization, upgrading of mutual association s, industrial chain development and industryindustry-city construction , to comprehensively promote the rural revitalization of border areas in the new